STP MARKETING STRATEGY ANALYSIS (SEGMENTING, TARGETING, AND POSITIONING) AND BUSINESS MODEL ON THE DEVELOPMENT OF MORTAR COMPANY BUSINESS UNITS (CASE STUDY AT PT. XY) - Djoko Santosa, ST (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
This research aims to establish STP (Segmenting, Targeting and Positioning) marketing strategies in marketing AAC Panel products. This research is qualitative research with descriptive methods. The subject in this study is PT XY which is engaged in mortar companies and the object of research is the STP marketing strategy (Segmentiing, Targetiing and Positioning) and business model for this business. From the analysis that has been carried out, researchers concluded that the segmenting strategy carried out by PT XY is based on geographic and demographic segmentation. The geographical segmentation of the intended sector is the sector, especially the western region of Java, while the demographic segmentation is a large contractor for high rise building types. For Targeting PT XY companies are mainly large contractors and industry experts. The positioning carried out by PT XY is by applying the production of modern and latest technology, namely flat-cake (horizontal cutting). Implementation of business model by joining venture at PT XY by considering the company's internal conditions.